The Impact of Market Orientation on Business Performance: Evidence from a Developing Country (Malaysian Management Journal, 2007)
The main aim of this paper is to investigate the relationship between market orientation and business performance. Hypothesis concerning the relationship between market orientation and business performance were posited and tested. Data were collected using a mail questionnaire survey approach. This study employed a simple random sampling procedure in selecting the organisations for inclusion in the sample. A total of 158 Malaysian manufacturing organisations participated in this study. Factor analysis, Pearson correlation, and multiple regression methods of data analysis were utilised for hypotheses testing. The results revealed that market focus, market action, market planning, market feedback, and market coordination jointly explained 32.6% of the variance of business performance. Market focus and market coordination were found to have statistically significant association with business performance. The outcome of this study provides vital information from a developing country perspective on the impact of market orientation practices on manufacturing organisations’ performance.